American Black Duck Anas rubripes and Mallard A. platyrhynchos abundance,occurrence of heterospecifi c pairing and wetland use between 1976 and 2003 in Northeastern Nova Scotia, Canada - Seymour, Norman R; Mitchell, Sean C (Wildfowl, 2013)
x.